Basic Body Awareness Therapy and patient education in hip osteoarthritis: a multiple case study. (2nd April 2016) - Strand, Liv Inger; Liland Olsen, Aarid; Nygard, Heid; Furnes, Ove; Heide Magnussen, Liv; Lygren, Hildegunn; Sundal, Mary Anne; Helvik Skjaerven, Liv
Abstract: International guidelines recommend exercise and patient education (PE) in hip osteoarthritis. However, we need more in-depth evidence regarding the effect of different exercise modalities. The aim of this study was to examine short- and long-term outcomes of PE and Basic Body Awareness Therapy (BBAT). Seven patients (five men, two women) with moderate to severe osteoarthritis were recruited. Pain, function and quality of life were assessed at baseline and after 4 and 10 months, pain during walking being the main outcome. PE, aiming for patients' empowerment through information and counselling, was given in a 2 h group setting. BBAT, focusing on promoting movement quality and awareness in a variety of daily movements, was given weekly in groups over 12 weeks. Five patients participated in PE and BBAT, two in PE only. After 4 months all reported improvement. Less pain during walking was found in four patients, and after 10 months in three patients (one PE, two PE and BBAT, two missing). One patient (PE) reported being unchanged and one (PE and BBAT) worse and motivated for surgery, both with 0 mm joint space. BBAT and PE may be beneficial in hip osteoarthritis, but the supplementary effect of BBAT must be further examined.